Recent Developments on Denitrogenative Functionalization of Benzotriazoles - Yu, Jie; Singh, Anoop S.; Yan, Guobing; Yu, Jian; Tiwari, Vinod K. (Synthesis, 2020)
Benzotriazoles are employed as useful synthons in organic synthesis, and due to their unique structural motif, they are able to undergo denitrogenation during the construction of new bonds. Various methods for the functionalization of benzotriazoles as precursors of ortho-amino arenediazoniums have recently been developed that involve transition-metal-catalyzed coupling reactions, mainly via cyclization, borylation, alkenylation, alkylation, carbonylation and the formation of carbon–heteroatom bonds. In this short review, we primarily focus on the recent applications of benzotriazoles in organic chemistry that proceed via a denitrogenative process, and the mechanisms are also discussed.1 Introduction2 Common Synthetic Routes Allowing Easy Access to Benzotriazole Derivatives3 Formation of C–C Bonds3.1 Cyclization Reactions3.2 Arylation, Alkenylation, Alkylation and Carbonylation Reactions4 Carbon–Heteroatom Bond Formation5 Miscellaneous Denitrogenative Functionalization6 Conclusions and Future Perspectives
Keywords: benzotriazoles; BtRC; ring cleavage; coupling reactions; denitrogenative functionalization